2003
DOI: 10.1143/jjap.42.l186
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Shock Tolerance of Ferroelectric Liquid Crystal Stabilized by Aligned Polymer Fibers

Abstract: The Fisher information matrix is employed in the gravitational-wave literature to quantify the statistical errors in estimating the parameters of gravitationalwave sources detectable by ground-based detectors. In particular, it is used to compute the lower bound on the variances of the parameters of the signals emitted by inspiralling compact binaries. However, the Fisher-matrix formalism is known to be valid in the strong-signal approximation only. Hence it is important to quantify the signal-to-noise ratio a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Transmittance through a pair of crossed polarizers sandwiching a FLC sample changes with the applied voltage and yields a hysteresis curve. When the FLC is completely bistable, the center of the optical hysteresis curve is 0 V. The deviation of the center of the hysteresis curve from 0 V means that the FLC exhibits a monostable state [14][15][16][17]. In the monostable state, the direction of spontaneous polarization is stabilized in one direction.…”
Section: Photorefractive Effect In Photoconductive-polymerstabilized mentioning
confidence: 99%
See 2 more Smart Citations
“…Transmittance through a pair of crossed polarizers sandwiching a FLC sample changes with the applied voltage and yields a hysteresis curve. When the FLC is completely bistable, the center of the optical hysteresis curve is 0 V. The deviation of the center of the hysteresis curve from 0 V means that the FLC exhibits a monostable state [14][15][16][17]. In the monostable state, the direction of spontaneous polarization is stabilized in one direction.…”
Section: Photorefractive Effect In Photoconductive-polymerstabilized mentioning
confidence: 99%
“…In the monostable state, the direction of spontaneous polarization is stabilized in one direction. The monostability of the direction of the spontaneous polarization is considered to be produced by the strong interaction between the FLC molecules and the mesogenic part of the polymer [16,17]. The electrooptical hysteresis of the mTPA-3=TNF=FLC mixture before and after UV irradiation was measured using the polarizing microscope (Fig.…”
Section: Photorefractive Effect In Photoconductive-polymerstabilized mentioning
confidence: 99%
See 1 more Smart Citation
“…Defect-free SS-FLC materials are desirable for a photorefractive material. It has been reported that a defect-free SS-state can be obtained using a polymerstabilized FLC [26,27]. The PS-FLC is formed through the photopolymerization of mesogenic acrylate monomer in an SS-state of a FLC in a 2 mm gap cell.…”
Section: Photorefractive Effect In Pps-flc Samplesmentioning
confidence: 99%
“…We have already clarified that some tolerance to thermal shock is introduced into smectic layers of devices containing polymer fibers. 7) Other approaches to obtaining a gray-scale operation of FLCs that include mechanisms for a monostable FLC operation have been found using various methods. These include usage of special FLC mixtures 8) such as anti-FLC, control 9) of high-pretilt alignment layers and FLC cone angles, and dispersion of micropolymers.…”
Section: Introductionmentioning
confidence: 99%